2021
DOI: 10.3390/antibiotics10050523
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Antibiotics Multidrug-Resistance Profile of Uropathogens in Romanian Population

Abstract: Urinary tract infections (UTIs) are a leading cause of morbidity for both males and females. The overconsumption of antibiotics in general medicine, veterinary, or agriculture has led to a spike in drug-resistant microorganisms; obtaining standardized results is imposed by standard definitions for various categories of drug-resistant bacteria—such as multiple-drug resistant (MDR), extensive drug-resistant (XDR), and pan drug-resistant (PDR). This retrospective study conducted in three university teaching hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
5
16
0
Order By: Relevance
“…This finding is in accordance with multiple recent studies [16][17][18][19], which found it to be the main etiological agent in up to 95% of the UTIs. The second most isolated bacteria were Klebsiella spp., encountered in 76 cases (21.4%), of which K. pneumoniae was by far the most common species, an aspect in accordance with the results reported by several recent studies [4,17,18,20], even though a recent study conducted in another region of Romania reported K. pneumoniae as the leading etiology in some settings [21].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is in accordance with multiple recent studies [16][17][18][19], which found it to be the main etiological agent in up to 95% of the UTIs. The second most isolated bacteria were Klebsiella spp., encountered in 76 cases (21.4%), of which K. pneumoniae was by far the most common species, an aspect in accordance with the results reported by several recent studies [4,17,18,20], even though a recent study conducted in another region of Romania reported K. pneumoniae as the leading etiology in some settings [21].…”
Section: Discussionsupporting
confidence: 89%
“…Even though Proteus spp. is usually associated with hospital-acquired UTIs [21], with higher resistance rates to carbapenems [40,41], we identified up to 97% susceptibility to meropenem, similar to other Romanian research [16]; however, we must interpret these results with caution, due to the relatively small number of Proteus spp. isolates.…”
Section: Discussionsupporting
confidence: 86%
“…The relevance of enterococci should not be underestimated, as they represented >20% of isolates, and the treatment options for these infections may be especially scarce in cases of extensive resistance. The increasing incidence of enterococci with the advanced age of the patients has been verified by other major studies previously; in addition, there has been evidence showing that patients affected by diabetes and/or metabolic disorder are significantly more susceptible to infections caused by Gram-positive cocci [12,22,29,30]. Additionally, the more precise identification method used in the second part of the study period (2013-2017) may also have had a role in the increased detection of enterococci, as it differentiates these isolates more successfully from other streptococci, which would have been dismissed as contaminants or colonizers by the clinical microbiologist and/or physician.…”
Section: Discussionsupporting
confidence: 66%
“…Overall, Escherichia coli (or uropathogenic E. coli [UPEC]) is the most frequently isolated species in UTIs [9]; nevertheless, in hospitalized and/or immunosuppressed patients, non-conventional urinary pathogens are increasingly present [10,11]. The antimicrobial therapy of UTIs has become increasingly challenging, due to worrying developments in antimicrobial resistance (AMR) worldwide [12]; clinicians are often left with scarce therapeutic choices, as multidrug-resistant (MDR) bacteria are progressively more common in both community-associated and healthcare-associated UTIs [13]. Extended-spectrum βlactamase (ESBL)-producing Enterobacterales, carbapenem-and fluoroquinolone-resistant Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…Hospitalization rates due to UTIs have also shown an increasing trend worldwide [22]. Although females of a reproductive age are the most commonly burdened with uncomplicated UTIs, the disease may affect anyone, irrespective of age, gender, or socio-economic status [23,24]. The most common causative agent in in both community-and hospital-associated UTIs is Escherichia coli, whereas Gram-negative bacteria are responsible for 80-90% of all UTIs overall [25].…”
Section: Introductionmentioning
confidence: 99%